Analysis of the forms the cooperation micro and small enterprises in the Slovak republic - Šúbertová, Elena; Gajdová, Denisa (Univerzita Pardubice, 2010)
Small-sized enterprises, often attached to their day-to-day routines, become incapable to innovate their products and processes and thus to look ahead with the aim to seize new market opportunities. One of the possibilities how to reduce disadvantages coming with the limited size of enterprises, is their joining together in order to better face their competitors and to extend their life at the market as well. The cooperation strategy and creation of clusters of micro and small-sized enterprises create conditions not only for the better access to loans for their own expansion but also provide better possibility of the effective use of the market place.
Keywords: franchising, cluster; contract; union; cooperation; co-operative